Determination of antiretroviral drugs for buyers' club in Switzerland using capillary electrophoresis methods. Issue 6 (28th December 2020) - Guichard, Nicolas; Tobolkina, Elena; El Morabit, Lamyae; Bonnabry, Pascal; Vernaz, Nathalie; Rudaz, Serge
Abstract: Human immunodeficiency virus‐acquired immunodeficiency syndrome continues to be a major global public health issue, having claimed almost 33 million lives to date. Due to the high cost of antiretroviral treatment, access to these drugs remains difficult for vulnerable populations, such as migrants and people living in prisons, who often do not have health insurance. These factors lead to poorer health outcomes and higher transmission rates. The personal importation scheme for unapproved generics from foreign countries is one option to access affordable human immunodeficiency virus treatment. However, the risk of importing falsified medicine remains high, and the quality control of unapproved drugs is lacking. In this context, three CE methods for the analysis of nine antiviral drugs found in commercial pharmaceutical formulations were evaluated. The selected compounds were emtricitabine, tenofovir disoproxil, tenofovir alafenamide, rilpivirine, efavirenz, raltegravir, dolutegravir, abacavir, and lamivudine. The developed methods were successfully applied to determine the active pharmaceutical ingredients of commercial formulations and unapproved generics. The quality control of unapproved generics by CE is an attractive approach due to its good standard of quality, low cost, ecofriendliness, and ease of implementation.